PENGARUH WORK-LIFE BALANCE DAN KONFLIK KERJA TERHADAP KINERJA KARYAWAN PEREMPUAN PT ENAMUL ENERGY UTAMA - Jannah, Tisa'ul; Harmen, Hilma (Jurnal Media Informatika, 2024)
This research aims to determine the effect of work-life balance and work conflict on the performance of female employees at PT Enamul Energy Utama. This research uses a quantitative approach. he population of this study was 132 female employees of PT Enamul Energy Utama. The sampling technique used is non-probability sampling with a purposive sampling method. The sample consisted of 132 people, namely all female employees of PT Enamul Energy Utama. The data analysis technique used is data quality testing, namely validity and reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing via the t test and f test and the coefficient of determination (R2). The research results show that Work-Life Balance (X1) partially has a negative and significant effect on the performance of female employees of PT Enamul Energy Utama, Work Conflict (X2) partially has a negative and significant effect on the performance of female employees of PT Enamul Energy Utama. Work-Life Balance (X1) and Work Conflict (X2) simultaneously have a negative and significant effect on the performance of female employees of PT Enamul Energy Utama.